The Impact of Podcasts on English Speaking Proficiency: A Controlled Experimental Study of EFL Learners - Lizamuddin, Ahmad; Zuhri, Mohammad Noor (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Speaking ability is one of the most challenging skills that English as a foreign language (EFL) learners must master. Along with the development of technology, media such as podcasts have become one of the promising alternatives to support speaking learning. This study examined the effect of using podcasts on improving EFL students' speaking ability through a quasi-experimental design. The research sample consisted of 60 students of English Education Study Program at Sultan Agung Islamic University who were divided into two groups: the experimental group (n=30) who received podcast-based learning and the control group (n=30) who underwent conventional learning. Pre-test and post-test were conducted to measure four main components of speaking ability, namely fluency, accuracy, pronunciation, and vocabulary range. The results showed that the experimental group experienced more significant improvements in all components than the control group. The t-test analysis showed significant differences (p < 0.05) in the post-test scores between the two groups, with greater improvement in the experimental group in terms of fluency (t = 3.5), accuracy (t = 2.9), pronunciation (t = 3.8), and vocabulary range (t = 3.2). These findings support Krashen's Input Hypothesis and Swain's Output Hypothesis, which suggest that podcasts provide authentic language input while encouraging active language production. This study suggests the integration of podcasts in EFL speaking learning and recommends further research in various other contexts.